Pengaruh Kualitas Produk, Market Driven Strategy dan Harga Terhadap Kepuasaan Pelanggan Batagor Mama Oki - Puty Nurusysyifa; Ika Suhartanti Darmo (UNIVERSITAS KALBIS, 2022)
The purpose of this study was to determine the effect of product quality, market driven strategy and price on customer satisfaction. This research is a quantitative research. The number of samples used is 115 people, with purposive sampling technique. The data comes from a Google Form questionnaire and the data is analyzed by SPSS 25. From the results of the analysis of the influence of product quality, market driven strategy and price, the effect on customer satisfaction of batagor mama oki.